Effects of combined creatine and sodium bicarbonate supplementation on repeated sprint performance in trained men - Barber, J. J.; McDermott, A. Y.; McGaughey, K. J.; Olmstead, J. D.; Hagobian, T. A. (The Journal of Strength and Conditioning Research, 2013)
Creatine and sodium bicarbonate supplementation independently increase exercise performance, but it remains unclear whether combining these 2 supplements is more beneficial on exercise performance. The purpose of this study was to evaluate the impact of combining creatine monohydrate and sodium bicarbonate supplementation on exercise performance. Thirteen healthy, trained men (21.1 ± 0.6 years, 23.5 ± 0.5 kg·m-2, 66.7 ± 5.7 ml/(kg·m)) completed 3 conditions in a double-blinded, crossover fashion: (a) Placebo (Pl; 20 g maltodextrin + 0.5 g/kg maltodextrin), (b) Creatine (Cr; 20 g + 0.5 g/kg maltodextrin), and (c) Creatine plus sodium bicarbonate (Cr + Sb; 20 g + 0.5 g/kg sodium bicarbonate). Each condition consisted of supplementation for 2 days followed by a 3-week washout. Peak power, mean power, relative peak power, and bicarbonate concentrations were assessed during six 10-second repeated Wingate sprint tests on a cycle ergometer with a 60-second rest period between each sprint. Compared with Pl, relative peak power was significantly higher in Cr (4%) and Cr + Sb (7%). Relative peak power was significantly lower in sprints 4-6, compared with that in sprint 1, in both Pl and Cr. However, in Cr + Sb, sprint 6 was the only sprint significantly lower compared with sprint 1. Pre-Wingate bicarbonate concentrations were significantly higher in Cr + Sb (10%), compared with in Pl and Cr, and mean concentrations remained higher after sprint 6, although not significantly. Combining creatine and sodium bicarbonate supplementation increased peak and mean power and had the greatest attenuation of decline in relative peak power over the 6 repeated sprints. These data suggest that combining these 2 supplements may be advantageous for athletes participating in high-intensity, intermittent exercise.